Clinical exercise physiology. - Ehrman, Jonathan K., 1962-; Gordon, Paul M., ....-; Visich, Paul S., ....- (Champaign : Human Kinetics, 2009)
And the neuromuscular system. This second edition also features an online ancillary package, allowing instructors to more effectively convey the concepts presented in the text and prepare students for careers in the field. Clinical Exercise Physiology, Second Edition, is easy to navigate-the logical order of the chapters makes key information easy to find. The detailed chapters discuss 23 disease states and conditions that clinical exercise physiologists encounter in their work and provide guidance for the expert care of the populations discussed. Each chapter covers the scope of the condition; its physiology and pathophysiology and treatment options; clinical considerations, including the administration of a graded exercise test; and exercise prescription. The text also details how clinical exercise physiologists can most effectively address issues facing special populations, including children, the elderly, and female athletes. Clinical Exercise Physiology, Second Edition, is the definitive
Clinical Exercise Physiology, Second Edition, provides a comprehensive look at the clinical aspects of exercise physiology by thoroughly examining the relationship between exercise and chronic disease. Updated and revised, this second edition reflects important changes that have occurred in the field since the first edition was published. It will provide professionals and students with fundamental knowledge of disease-specific pathology and treatment guidelines while also guiding readers through the clinical exercise physiology associated with exercise testing and training of patients with a chronic disease. The second edition of Clinical Exercise Physiology builds on information presented in the previous edition with reorganized chapters, updated and revised content, and the latest information on the key practice areas of clinical exercise physiology: endocrinology, the metabolic system, the cardiovascular system, the respiratory system, oncology, the immune system, bone and joint health
Disease Chapter 22. Asthma Chapter 23. Cystic Fibrosis Part VI. Oncology and the Immune System Chapter 24. Cancer Chapter 25. Human Immunodeficiency Virus Part VII. Disorders of the Bone and the Joints Chapter 26. Arthritis Chapter 27. Osteoporosis Chapter 28. Nonspecific Low Back Pain Part VIII. Selected Neuromuscular Disorders Chapter 29. Spinal Cord Injury Chapter 30. Multiple Sclerosis Chapter 31. Cerebral Palsy Chapter 32. Stroke
Inhoudsopgave : (verkort) Part I. Introduction to Clinical Exercise Physiology Chapter 1. Introduction Chapter 2. Behavioral Approaches to Physical Activity Promotion Chapter 3. Pharmacotherapy Chapter 4. General Evaluation and Examination Skills Chapter 5. Graded Exercise Testing and Exercise Prescription Part II. Special Populations Chapter 6. Children Chapter 7. The Elderly Chapter 8. Female-Specific Issues Chapter 9. Depression and Exercise Part III. Endocrinology and Metabolic Disorders Chapter 10. Metabolic Syndrome Chapter 11. Diabetes Chapter 12. Obesity Chapter 13. Hypertension Chapter 14. Hyperlipidemia and Dyslipidemia Chapter 15. End-Stage Renal Disease Part IV. Cardiovascular Diseases Chapter 16. Myocardial Infarction Chapter 17. Revascularization of the Heart Chapter 18. Chronic Heart Failure Chapter 19. Peripheral Arterial Disease Chapter 20. Pacemakers and Internal Cardiac Defibrillators Part V. Diseases of the Respiratory System Chapter 21. Chronic Obstructive Pulmonary
Of prescribing exercise
Resource on the use of exercise training for the prevention and treatment of clinical diseases and disorders. It includes the following features: * Revised and updated content reflects the recent changes in exercise testing and training principles and practices. * Four new chapters on depression and exercise, metabolic syndrome, cerebral palsy, and stroke are evidence of how the field has evolved in considering patients with more widely diagnosed diseases and conditions. * A new text-specific Web site containing a test package and PowerPoint presentation package helps instructors present the material from the book. * Case studies provide real-world examples of how to use the information in practice. * Discussion questions that highlight important concepts appear throughout the text to encourage critical thinking. * Practical application boxes offer tips on maintaining a professional environment for client-clinician interaction, a literature review, and a summary of the key components
Keywords: Clinical exercise physiology; Exercise Therapy -- Case Reports; Exercise therapy; Exercise -- Physiological aspects; Exercise -- Physiology -- Case Reports; Fysiologie; Lichamelijke inspanning; Oefentherapie